A Nonsense Mutation in TLR5 Is Associated with Survival and Reduced IL-10 and TNF-α Levels in Human Melioidosis - Chaichana, P; Chantratita, N; Brod, F; Koosakulnirand, S; Jenjaroen, K; Chumseng, S; Sumonwiriya, M; Burtnick, M; Brett, P; Teparrukkul, P; Limmathurotsakul, D; Day, N; et al. (Public Library of Science, 2017)
Background Melioidosis, caused by the flagellated bacterium Burkholderia pseudomallei, is a life-threatening and increasingly recognized emerging disease. Toll-like receptor (TLR) 5 is a germline-encoded pattern recognition receptor to bacterial flagellin. We evaluated the association of a nonsense TLR5 genetic variant that truncates the receptor with clinical outcomes and with immune responses in melioidosis. Methodology/Principle Findings We genotyped TLR5 c.1174C>T in 194 acute melioidosis patients in Thailand. Twenty-six (13%) were genotype CT or TT. In univariable analysis, carriage of the c.1174C>T variant was associated with lower 28-day mortality (odds ratio (OR) 0.21, 95% confidence interval (CI) 0.05-0.94, P = 0.04) and with lower 90-day mortality (OR 0.25, 95% CI 0.07-086, P = 0.03). In multivariable analysis adjusting for age, sex, diabetes and renal disease, the adjusted OR for 28-day mortality in carriers of the variant was 0.24 (95% CI 0.05-1.08, P = 0.06); and the adjusted OR for 90-day mortality was 0.27 (95% CI 0.08-0.97, P = 0.04). c.1174C>T was associated with a lower rate of bacteremia (P = 0.04) and reduced plasma levels of IL-10 (P = 0.049) and TNF-α (P < 0.0001). We did not find an association between c.1174C>T and IFN-γ ELISPOT (T-cell) responses (P = 0.49), indirect haemagglutination titers or IgG antibodies to bacterial flagellin during acute melioidosis (P = 0.30 and 0.1, respectively). Conclusions/Significance This study independently confirms the association of TLR5 c.1174C>T with protection against death in melioidosis, identifies lower bacteremia, IL-10 and TNF-α production in carriers of the variant with melioidosis, but does not demonstrate an association of the variant with acute T-cell IFN-γ response, indirect haemagglutination antibody titer, or anti-flagellin IgG antibodies.